Differences in explosive strength of elite female handball players during the competition season - Bojic, I.; Zivkovic, M.; Kocic, M.; Velickovic, M.; Milenkovic, D. (Facta Universitatis: Series Physical Education and Sport, 2019)
The aim of our research was to determine the explosive strength of the legs i.e., the height of the jump of the top-ranked female handball players during the season. 15 female players underwent the following tests for estimating the explosive strength of the legs: SJ, CMJ, CMJ free arm, CMJ right leg and CMJ left leg. The Student`s t-test was applied for establishing the changes between the measuring sessions during the season. The results obtained show that there were statistically significant changes and better results at the end of the season in the following parameters: CMJ right leg =.002 and CMJ left leg = .018, whereas no significant changes occurred in all the other two-leg jumps. Taking into consideration the fact that in performing different throws and goal shooting the most prominent movements in handball are done on one leg, the results were expected. It is recommended that throughout the season the training process should include additional exercises for improving and maintaining the ability of the handball players to jump (plyometric, proprioceptive and the combination of the two with the common strength improving exercises), since their positive effects have been proven by quite a few studies.